Use of Adjuvants to Optimize the Activity of Two Broad-Spectrum Herbicides for Weed Control in Wheat - ABBAS,N. (2018)
ABSTRACT: Herbicide resistance development among weeds, environmental contamination and health concerns due to the overuse of herbicides have led researchers to focus on ways to reduce herbicides to be sprayed for weed management. Adjuvants are best suited for that purpose, as they accomplish a crucial role in achieving satisfactory control of weeds by maximizing herbicidal activity. A two-year field investigation was carried out at the Agronomic Research Area, in the University of Agriculture, in Faisalabad, Pakistan during the winter of 2014 and 2015, with the objective to optimize the activity of two broad-spectrum herbicides at reduced dose (75% of the label mentioned rate) for weed control in wheat. Minimum weed density, weed dry weight and NPK uptake were recorded with reduced dosed mesosulfuron methyl + iodosulfuron methyl sodium at 10.60 g a.i. ha-1 combined with fatty alcohol ethoxylate at 200 mL ha-1. This was followed by reduced dosed sulfosulfuron at 18.75 g a.i. ha-1 combined with the same adjuvant. Among various herbicidal treatments, application of reduced dosed mesosulfuron methyl + iodosulfuron methyl sodium at 10.60 g a.i. ha-1 combined with fatty alcohol ethoxylate at 200 mL ha-1 was proved to be most cost effective and resulted in maximum wheat yield during both years of study.